2000
DOI: 10.1128/jb.182.16.4384-4393.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the nfrA-ywcH Operon from Bacillus subtilis Is Specifically Induced in Response to Heat

Abstract: The NfrA protein, an oxidoreductase from the soil bacterium Bacillus subtilis, is synthesized during the stationary phase and in response to heat. Analysis of promoter mutants revealed that the nfrA gene belongs to the class III heat shock genes in B. subtilis. An approximate 10-fold induction at both the transcriptional and the translational levels was found after thermal upshock. This induction resulted from enhanced synthesis of mRNA. Genetic and Northern blot analyses revealed that nfrA and the gene downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…RNA was isolated from the stressed and unstressed bacteria and was subjected to Northern blot analyses and RT-PCR. In contrast to nfrA expression in B. subtilis (24), no induction of nfrA was observed in response to heat in S. aureus (Fig. 4).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…RNA was isolated from the stressed and unstressed bacteria and was subjected to Northern blot analyses and RT-PCR. In contrast to nfrA expression in B. subtilis (24), no induction of nfrA was observed in response to heat in S. aureus (Fig. 4).…”
Section: Resultsmentioning
confidence: 73%
“…Regulation of nfrA expression by use of different sigma factors in B. subtilis, however, is still being investigated since Moch et al have identified putative SigA-, SigB-, and SigD-dependent promoter sequences in front of the nfrA gene. Moreover, heat induction of nfrA was still observed in a SigB-and SigD-deficient strain and also in a CtsR-and HrcA-deficient strain (24).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations